Pengaruh Ketebalan Terhadap Daya Serap Energi Impak pada Rompi Anti Peluru yang Terbuat dari Komposit Hgm-Epoxy Dan Serat Karbon - Muhammad Anhar Pulungan; Sutikno Sutikno (LPPM Politeknik Aceh Selatan, 2017)
Bulletproof vests are outer clothing commonly used to protect military personnel from projectile attacks and explosion material distributions. In this study the bulletproof vests were made of composite particles composed of an epoxy matrix with a Hollow Glass Microsphere (HGM) amplifier and carbon fiber. The study was conducted by doing simulation analysis using Finite Element Method in accordance with NIJ (National Institute of Justice) of American Standard 0101.06 for class IIIA weapons category. The thickness of bulletproof vest was varied from 1 to 20 mm in order to obtain the optimal thickness. After obtaining optimal thickness of the bulletproof vest, then verification with experimental will be done to validate the simulation result. The results showed that the increase in the thickness has increase the toughness and rigidity of a bulletproof vest. A bulletproof vest with a thickness of 20 mm able to absorb bullet energy of 348.27 Joule and kinetic energy which passed the body of 138, 77 Joule with a penetration depth of 5.54 mm. Thus, it has met the NIJ Standard 0101.06 standard of U.S. The energy passed to the body is smaller than 170 Joule.